The Role of Social Workers in Empowering Poor Village Communities: Study of Indonesian Conditional Cash Transfer Programme (PKH) Facilitators in Jegulo Village, Tuban Regency - Denny Iswanto (Jurnal Administrasi Karya Dharma, 2023)
The first poverty alleviation program in the form of social transfers in Indonesia is the Family Hope Program (PKH). PKH is a conditional social assistance program for poor and vulnerable families and/or individuals who are registered with integrated data on the program for handling the poor, processed by the Social Welfare Data and Information Center and designated as PKH beneficiary families. The Family Hope Program (PKH) can be said to be a community empowerment program because its goals and targets are directly aimed at improving the economy, education and health. The purpose of this study was to analyze the role of PKH assistants in the empowerment process. This research uses descriptive qualitative research. The results of the study indicate that an empowerment process has been carried out in facilitating beneficiaries in accessing social, education and health services. In addition, the assistant also carries out community capacity building through business assistance. In carrying out the role as a mediator between the beneficiary communities and the government in fighting for the rights of beneficiaries properly. In carrying out its role in advocating and advocating for recipient communities, it is carried out inclusively, fighting for the rights of beneficiaries, both from the poor, persons with disabilities and persons with mental disorders who also have rights as recipients of social assistance.